Hypopigmented large-cell acanthoma of the eyelid - A. Tulin Mansur; Ikbal E. Aydingoz; Ali Kupelioglu; Emel Dikicioglu Cetin (Wolters Kluwer Medknow Publications, 2012)
Large-cell acanthoma is an asymptomatic, slightly keratotic, usually hyperpigmented epidermal lesion that is mostly seen in the sun-exposed skin of middle-aged or elderly people. It is characterized by extraordinarily large keratinocytes that can reach up to twice their normal size without a change in the nucleus/cytoplasm ratio. Here, we describe a chronic case of large-cell acanthoma that involved the whole upper eyelid of a 67-year-old man for at least 15 years. The lesion was almost depigmented and demonstrated altered consistency of the eyelid, causing lax and folded skin. The lesion responded to treatment with topical tretinoin and urea. This case verifies the benign character of large-cell acanthoma and demonstrates how it may have atypical presentations.